The anterior cingulate cortex and pain processing - Fuchs, Perry N.; Peng, Yuan Bo; Boyette-Davis, Jessica A.; Uhelski, Megan L. (Frontiers in Integrative Neuroscience, 2014)
The neural network that contributes to the suffering which accompanies persistent pain states involves a number of brain regions. Of primary interest is the contribution of the cingulate cortex in processing the affective component of pain. The purpose of this review is to summarize recent data obtained using novel behavioral paradigms in animals based on measuring escape and/or avoidance of a noxious stimulus. These paradigms have successfully been used to study the nature of the neuroanatomical and neurochemical contributions of the anterior cingulate cortex to higher order pain processing in rodents.